(untitled) (Observatorio Económico, 2013)
There is a certain type of good that is desirable for society as a whole, yet citizens oppose having it near their place of residence (global benefits and local costs). The most common examples are landfills, power plants, airports, and the like. Because of the nature of these goods, the economics literature refers to them as NIMBY (“not in my backyard”). This feature of NIMBY goods can give rise to serious problems, such as underinvestment in infrastructure or in the capital required for the development of the economy. Continue reading...